A case report of a patient with recurrent and severe infections highlighting the importance of considering inborn errors of immunity - Altammar, Fajer; Alshamali, Mohammed; Alqunaee, Marwan; Alali, Ahmad J.; Elshafie, Reem M.; Al-Herz, Waleed (Frontiers in Pediatrics, 2024)
Inborn errors of immunity (IEI) can often be misdiagnosed early in life due to their heterogenous clinical presentations. Interleukin-1 receptor-associated kinase 4 (IRAK-4) deficiency is one of the rare innate immunodeficiency disorders. We present the case of a patient who presented at the age of 15 days with meningitis and septic shock that responded to antibiotics. She was admitted again at the age of 45 days with pseudomonas aeruginosa bacteremia that was associated with increased inflammatory markers. Her third admission was at the age of 2.5 months due to left sided peri-orbital cellulitis that was again associated with elevated inflammatory markers. At 3.5 months, she experienced left orbital cellulitis, which was complicated by extensive sinus involvement, erosion, and abscess formation in the pterygopalatine fossa. Her condition progressed to septic shock and required multiple antibiotics and surgical interventions for drainage and control of the infection source. Both abscess and blood culture were positive for pseudomonas aeruginosa. An IEI was suspected but basic immunology testing was normal. Whole Exome Sequencing was performed and a novel mutation in IRAK4 was detected. In conclusion, we highlight the importance of raising awareness among pediatricians about the potentially lethal IEI and the need to consult specialists when these diseases are suspected. Among them is IRAK-4 deficiency which can be diagnosed by sophisticated functional assays and/or genetic testing.